1993
DOI: 10.1007/bf00166739
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent nimodipine attenuates the withdrawal signs and the increase of cerebral dihydropyridine binding after chronic morphine treatment in rats

Abstract: The effect of chronic administration of dihydropyridine calcium channel antagonist nimodipine (1 mg/kg/day) given concurrently with morphine on the signs of morphine withdrawal and on the [3H]nitrendipine binding in the rat brain has been investigated. Chronic morphine administration in increasing daily doses from 20 mg/kg to 70 mg/kg for 24 days and consequent withdrawal for 24 h induced loss of body weight, wet dog shakes, episodes of writhing and yawning behaviour. The density of [3H]nitrendipine binding wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…In rats an increased DHP binding induced by prolonged opioid treatment was localized to the cortex, hippocampus and brainstem but not to the cerebellum and striatum (Ramkumar and El-Fakahany, 1988). These data were confirmed by Zharkovsky et al (1993), who reported that in rats concurrent nimodipine treatment prevented the rise in the density of central DHP binding sites which occurred during chronic treatment. The authors suggest that chronic nimodipine treatment attenuates the development of withdrawal symptoms which occur on termination of chronic morphine treatment by preventing the upregulation of central DHP-sensitive binding sites.…”
Section: Preclinical Datasupporting
confidence: 77%
“…In rats an increased DHP binding induced by prolonged opioid treatment was localized to the cortex, hippocampus and brainstem but not to the cerebellum and striatum (Ramkumar and El-Fakahany, 1988). These data were confirmed by Zharkovsky et al (1993), who reported that in rats concurrent nimodipine treatment prevented the rise in the density of central DHP binding sites which occurred during chronic treatment. The authors suggest that chronic nimodipine treatment attenuates the development of withdrawal symptoms which occur on termination of chronic morphine treatment by preventing the upregulation of central DHP-sensitive binding sites.…”
Section: Preclinical Datasupporting
confidence: 77%
“…ACTH and physostigmine) [22,89] suggests that μ-opioid receptors in other brain regions may also be involved in the tonic inhibition of yawning. In addition, it is interesting to note that increases in yawning have been used for the identification and characterization of morphine withdrawal in humans and laboratory animals dating back to the 1930s [91][92][93].…”
Section: Opioidsmentioning
confidence: 99%
“…Ca 2+ antagonists increase the acute analgesic effects of opioids in humans (von Bormann et al 1985) and in rodents (Hoffmeister and Tettenborn 1986;Dierssen et al 1990;Díaz et al 1995a), whereas Ca 2+ channel activators, such as Bay K 8644, antagonised opioid antinociception (Dierssen et al 1990). Furthermore, Ca 2+ channel blockers have been shown to reduce the expression of opioid tolerance in humans (Santillán et al 1994(Santillán et al , 1998 and in rats (Dierssen et al 1990;Díaz et al 1995a;Michaluk et al 1998), and attenuate the withdrawal syndrome that is seen after chronic opioid administration (Bongianni et al 1986;Baeyens et al 1987; Barrios and Baeyens 1988;Pellegrini-Giampietro et al 1988;Alfaro et al 1990;Antkiewicz-Michaluk et al 1990, 1993Colado et al 1993;Zharkovsky et al 1993Zharkovsky et al , 1999Michaluk et al 1998).…”
Section: Introductionmentioning
confidence: 97%